Tourism as Soft Power: Political Crises and Nation Branding in the Philippines (2008–2025) - Noel Y. Sinco (ASEAN Journal on Hospitality and Tourism, 2026)
This study examines the relationship between political crises and international tourist arrivals to the Philippines (2008–2025) using multi-country Interrupted Time Series Analysis (ITSA). Major events—including the 2010 Manila Hostage Crisis, 2012 Scarborough Shoal standoff, 2013 Taiwanese Fisherman Incident, and 2017 Marawi siege—are analyzed across key source markets. Descriptive patterns indicate short-term bilateral fluctuations aligned with crisis events, particularly in markets directly involved in diplomatic disputes. However, ITSA's estimates do not detect statistically significant structural breaks in aggregate arrivals, suggesting the absence of sustained level or trend shifts. Western markets such as the United States, Canada, and Australia exhibit no statistically detectable post-crisis changes following the Marawi siege. Recovery periods, defined as the return to pre-crisis annual levels, generally reflect short-term adjustment rather than prolonged contraction. Overall, findings indicate temporary volatility alongside aggregate tourism resilience.